Fidelity evaluation of the dialogue around respiratory illness treatment (DART) program communication training. Issue 7 (July 2022) - Mangione-Smith, Rita; Robinson, Jeffrey D.; Zhou, Chuan; Stout, James W.; Fiks, Alexander G.; Shalowitz, Madeleine; Gerber, Jeffrey S.; Burges, Dennis; Hedrick, Benjamin; Warren, Louise; Grundmeier, Robert W.; Kronman, Matthew P.; et al.
Abstract: Objective: To evaluate receipt fidelity of communication training content included in a multifaceted intervention known to reduce antibiotic over-prescribing for pediatric acute respiratory tract infections (ARTIs), by examining the degree to which clinicians implemented the intended communication behavior changes. Methods: Parents were surveyed regarding clinician communication behaviors immediately after attending 1026 visits by children 6 months to < 11 years old diagnosed with ARTIs by 53 clinicians in 18 pediatric practices. Communication outcomes analyzed were whether clinicians: (A) provided both a combined (negative + positive) treatment recommendation and a contingency plan (full implementation); (B) provided either a combined treatment recommendation or a contingency plan (partial implementation); or (C) provided neither (no implementation). We used mixed effects multinomial logistic regression to determine whether these 3 communication outcomes changed between baseline and the time periods following each of 3 training modules. Results: After completing the communication training, the adjusted probability of clinicians fully implementing the intended communication behavior changes increased by an absolute 8.1% compared to baseline (95% Confidence Interval [CI]: 2.4%, 13.8%, p = .005). Conclusions: Our findings support the receipt fidelity of the intervention's communication training content. Practical implications: Clinicians can be trained to implement communication behaviors that may aid in reducing antibiotic over-prescribing for ARTIs. Highlights: Pediatric antibiotic over-prescribing for acute respiratory illnesses is common. Clinician communication is associated with inappropriate antibiotic prescribing. Communication training can successfully change clinician communication behaviors.